Наукові праці МАУП. Юридичні науки. Вип. 1 (77) - Міжрегіональна Академія управління персоналом (My University, 2026)
У збірнику наукових праць публікуються статті науковців, які досліджують актуальні проблеми розвитку права. Для науковців, викладачів, студентів, а також усіх, кого цікавить розвиток науки в Україні. The collection of scientific works publishes articles by scientists who investigate current problems of the development of law. For scientists, teachers, students, as well as everyone who is interested in the development of science in Ukraine.